Modeling of the Flexible Electronics Technologies - Balaišis, P.; Eidukas, D.; Žickis, A. (Elektronika ir Elektrotechnika, 2007)
The structural scheme of flexible electronic technologies (ET) was formed. Main directions for investigations of these technologies were pointed out. Main ET development peculiarities, the dependence of the flexibility degree on the intensity of application and the dynamics principles of these technologies were analyzed. When synthesizing flexible ET the method of hierarchy formation of controlled frames is used. ET task accomplishment probability was selected as the index of the flexible ET technical efficiency. Flexible ET efficiency evaluation method was created using the frame hierarchy and its control schemes. The offered method provides the possibilities to calculate generalized efficiency of all ET of the selected area and (or) branch. Ill. 13, bibl. 5 (in English; summaries in English, Russian and Lithuanian).